Kesiapan Guru Terhadap Pembelajaran Diferensiasi - Fakhirah; Nurul Amaliah; Ernawati (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
Differentiated learning is a way of understanding and providing knowledge according to the talents and learning styles of students who have many characters. This research aims to describe the implementation of differentiated learning at SMK 1 Maros and Sekolah Putri Darul Istiqamah (SPIDI). This research uses qualitative with descriptive research type. The sources of this research are English teachers at SMK 1 Maros and Biology teachers at Sekolah Putri Darul Istiqamah (SPIDI). The data collection methods used were interview, observation, and documentation. Data analysis techniques used in this research are data reduction, data presentation and conclusion drawing. The results showed that teachers in both schools understand the concept of differentiated learning and its importance to meet students' diverse learning needs. The challenges faced by teachers in both schools include the diversity of student learning, the need for more time to prepare learning materials, and difficulties in managing the classroom. Teachers in both schools have also developed various solutions to overcome these challenges, such as collaboration with stakeholders, using technology, and providing varied tasks. The conclusion from this study is that student-focused differentiated learning is worth implementing as it is an effective strategy to meet students' diverse learning needs.